2016
DOI: 10.1089/acm.2015.0066
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acupuncture on Cerebral Blood Flow in Post-Stroke Patients: A Randomized Controlled Trial

Abstract: Background/Objective: Stroke is a major cause of disability and death in the Western world. Studies have shown a direct relationship between specific mental and motor activity and changes in cerebral blood flow. Acupuncture is often used in post-stroke patients, but there is a lack of sham-controlled studies evaluating the effects of acupuncture on cerebral blood flow following a stroke. This pilot concept-assessment study sought to evaluate the effects of true acupuncture on cerebral blood flow velocity compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 18 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…10 11 Combining acupuncture and Chinese herbal medicine may more comprehensively improve post-stroke symptoms and may be more reflective of the clinical strategy most commonly applied in the field. Acupuncture has significant effects on cerebral vascular flow and flow velocity to both hemispheres of the brain, 12 and may reduce the volume of Original paper injury between the hemispheres, according to PET studies. 13 Acupuncture and electroacupuncture may also reduce cognitive impairment in rats through the regulation of expression of apoptosis-related genes, Bcl-2 and Bax, 14 and has been shown to markedly suppress the generation of free radicals after just 2 weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…10 11 Combining acupuncture and Chinese herbal medicine may more comprehensively improve post-stroke symptoms and may be more reflective of the clinical strategy most commonly applied in the field. Acupuncture has significant effects on cerebral vascular flow and flow velocity to both hemispheres of the brain, 12 and may reduce the volume of Original paper injury between the hemispheres, according to PET studies. 13 Acupuncture and electroacupuncture may also reduce cognitive impairment in rats through the regulation of expression of apoptosis-related genes, Bcl-2 and Bax, 14 and has been shown to markedly suppress the generation of free radicals after just 2 weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In modern medicine, studies indicate that acupuncture can reduce discomforts of vertigo and decreases neurological impairment. A pilot study showed that acupuncture could improve cerebral blood flow velocity in poststroke patients, [ 21 ] and animal experiment reveals that acupuncture effectively promoted cerebral perfusion of ischemic rats. [ 31 ] Systematic and literature reviews have reported the beneficial effect of acupuncture treating stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 15 ] Clinical and laboratory studies show that acupuncture is safe and has therapeutic effect for ischemic stroke and vertigo patients [ 16 19 ] Acupuncture reduces discomforts of vertigo and decreases neurological impairment through prompting cerebral blood flow. [ 20 , 21 ] However, systematic review that focuses on efficacy of acupuncture for PCIV is lacked. Based on these, we aim to evaluate the efficacy and safety of acupuncture for PCIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…An additional meta‐analysis that evaluated the effect of Baihui (CV20)‐based scalp acupuncture in animal models of focal cerebral ischaemia concluded that this treatment approach could improve infarct volume and exert a potential neuroprotective role in experimental ischaemic stroke . A recent study that evaluated the effect of acupuncture on cerebral blood flow in post‐stroke patients might also support the use of acupuncture in this condition.…”
Section: Commentarymentioning
confidence: 99%